Differential expression of genes in clinical strains of mycobacterium tuberculosis in response to isoniazid - Seepe, Prudy Mashika (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.